Comparison of maintenance effect of probiotics and aminosalicylates on ulcerative colitis: A meta-analysis of randomized controlled trials. Issue 1 (March 2016) - Jiang, Yong; Zhang, Zhi-Guang; Qi, Feng-Xiang; Zhang, Ying; Han, Tao
Abstract: Objective: To evaluate the maintenance effect of probiotics versus that of aminosalicylates on ulcerative colitis. Methods: MEDLINE, EMBASE, the Cochrane Controlled Trials Register, and the Chinese Biomedical Database were searched in English or Chinese. Data extracted were selected with strict criteria. Results: In six randomized controlled trials (RCTs), a total of 721 participants were enrolled and the maintenance effect of probiotics ( n = 364) versus that of aminosalicylates ( n = 357) on ulcerative colitis was investigated. No significant difference was observed between probiotics and aminosalicylate groups (relative risk ( RR ) = 1.08; 95% confidence interval ( CI ): 0.91–1.28; P = 0.40). Three RCTs compared the incidence of adverse events with probiotics versus those with aminosalicylates. No significant difference was observed in the incidence of adverse events between the two groups ( RR = 1.20; 95% CI : 0.92–1.56; P = 0.17). Conclusions: Probiotics and aminosalicylates both showed a maintenance effect on ulcerative colitis. However, more well-designed RCTs are required.